2021
DOI: 10.1080/13696998.2021.1939705
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of healthcare resource utilization and costs of patients with HR+/HER2- advanced breast cancer treated with ribociclib versus other CDK4/6 inhibitors

Abstract: This study was sponsored by Novartis Pharmaceuticals Corporation. The study sponsor was involved in several aspects of the research including the study design, the interpretation of data, the writing of the manuscript, and the decision to submit the manuscript for publication. Declaration of Financial/Other InterestsSB, RS, and MLP are employees and stockholders of Novartis Pharmaceuticals Corporation. RB, AG, and RB are employees of Analysis Group, Inc., a consulting company that has provided paid consulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In conclusion, to our knowledge, this study has the longest follow up of any abemaciclib observational study, and is the first one, outside of the clinical trial setting, to obtain OS data with abemaciclib [ 18 , 19 ]. Baseline characteristics of women treated within the NPU program suggest an advanced disease course and worse prognosis than in patients enrolled in abemaciclib clinical trials, with a heavily pre-treated population, a high tumor load, and a high proportion of patients with bone and visceral disease.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, to our knowledge, this study has the longest follow up of any abemaciclib observational study, and is the first one, outside of the clinical trial setting, to obtain OS data with abemaciclib [ 18 , 19 ]. Baseline characteristics of women treated within the NPU program suggest an advanced disease course and worse prognosis than in patients enrolled in abemaciclib clinical trials, with a heavily pre-treated population, a high tumor load, and a high proportion of patients with bone and visceral disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that palbociclib, the first approved medicine of the 3 CDK4/6 inhibitors, remained the predominant medicine that was prescribed. This preference for palbociclib was also seen in other high-income countries, although there is no clear evidence that palbociclib is superior to ribociclib and abemaciclib . Possibly the pattern of use can be explained by physician preferences, the marketing strategies of the manufacturers, hospital policies, or differences in price rebates.…”
Section: Discussionmentioning
confidence: 90%
“…This preference for palbociclib was also seen in other high-income countries, although there is no clear evidence that palbociclib is superior to ribociclib and abemaciclib. [38][39][40][41][42] Possibly the pattern of use can be explained by physician preferences, the marketing strategies of the manufacturers, hospital policies, or differences in price rebates. We also observed that the CDK4/6 inhibitors were mainly combined with fulvestrant, which likely reflects the recommendation in the Netherlands to primarily prescribe CDK4/6 inhibitors in the second line of treatment.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%